Securing cloud services : a pragmatic approach to security architecture in the cloud - Newcombe, Lee (IT Governance Pub., 2012)
This book provides an overview of security architecture processes and explains how they may be used to derive an appropriate set of security controls to manage the risks associated with working in the Cloud.